Transient leg deformations during eclosion out of a tight confinement: A comparative study on seven species of flies, moths, ants and bees. Issue 4 (July 2017) - Frantsevich, Leonid; Kozeretska, Iryna; Dubrovsky, Yuriy; Markina, Tetyana; Shumakova, Iryna; Stukalyuk, Stanislav
Abstract: Legs in dipteran pupae are tightly packed in a zigzag configuration. Changes in the shape or configuration of long podomeres during eclosion have been overlooked because they occur rapidly (in a few minutes) and the legs are hidden inside a tight opaque confinement: the puparium in the Cyclorrhapha, the obtect pupa in mosquitoes. We fixed insects at different times during eclosion and obtained a temporal description of changes in leg shape. At the start of eclosion in Calliphora vicina and Drosophila melanogaster, femora are buckled in between the joints. Later, the chain of podomeres straightened, pointing posterad. Initial deformation and further stretching were passive, exerted by forces external to the legs. The prerequisites for this are pliability of the tubular podomeres and anchoring of the tarsi to the confinement. Each femur was strongly crooked instead of buckled in the mosquito Aedes cantans . The site of bending shifted distad in the course of eclosion: a sort of peeling. In contrast, other insects (the moth Bombyx mori, the ants Formica polyctena and Formica rufa, the honey bee Apis mellifera ) left their tight confinements without any change in the initial zigzag leg configuration and without transient deformations of initially straight femora and tibiae. Graphical abstract: Highlights: Legs in insect pupae are tightly packed in zigzag configuration. During eclosion in flies, legs are stretched into straight chains of podomeres. Each femur turns about 90° inside the tight puparium or exuvium. This turn is facilitated by buckling or steep bending amidst the femur. No podomere deformation or leg stretching occurs in a moth, in a bee or in ants.